How radio and chemotherapy can affect the development of the teeth - Rio, Maria Ivanda Rabelo do; Rodrigues, Davi Ramos; Lyra, Marina Lima; Freire, Nathália de Almeida; Ramos, Maria Eliza Barbosa; Israel, Mônica Simões (Journal of Oral Diagnosis, 2023)
Introduction: The evolution of chemo and radiotherapy, added to the increased frequency in its use, have led to an increase in the survival rate of pediatric patients with head and neck cancer. Thus, the effects of this therapy are increasingly common, and may affect even the teeth in formation. Objective: Conduct a literature review on the main dental anomalies of development in patients undergoing chemo and radiotherapy. Material and methods: The databases “Pubmed”, “Google Scholar” and “Science Direct” were consulted using the keywords “dental alterations”, “children”, “dentistry”, “cancer”, “chemotherapy” and “ radiotherapy”. Twenty-seven articles published in English were selected. Results: Based on the articles included in the study, the effects of chemoradiotherapy on developing teeth can be both quantitative and qualitative. Those patients who underwent treatment during childhood, in this literature review, were between 0.8 and 15 years old. The main dental anomalies found include microdontia, hypodontia and root anomalies. In addition, it was also observed that the late effects of the therapy vary according to the radiation dose and the chemotherapy dose. Conclusions: Although there are few studies on dental alterations caused by chemotherapy and radiotherapy, it is necessary to implement protocols aimed at oral care during and after treatment to reduce the incidence and severity of such complications.